Development and efficiency of the banking sector in a transitional economy: Hungarian experience - Iftekhar Hasan; Katherin Marton (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
The paper analyzes the experiences and developments of Hungarian banking sector during the transitional process from a centralized economy to a market-oriented system.The paper identifies that early reorganization initiatives, flexible approaches to privatization, and liberal policies towards foreign banks involvement with the domestic institutions helped to build a relatively strong and increasingly efficient banking system.Banks with higher foreign bank ownership involvement were associated with lower inefficiency.
URN:NBN:fi:bof-201408071972
Keywords: 330